Sie sind auf Seite 1von 2

[Marks]

[4]

[4]

[4]

[4]

[7]

[7]

MATH 3705B Test 1 Solutions

January 23, 2012

1. L e cos(3 t) s 2

(a)

( s 2) 2 Answer: (a)

2t

=

+ 9

(b)

s

( s 2) 2 + 9

s + 2

(c) ( s + 2) 2 + 9

s 2

(d) s 2 + 9

(e) None of these

2.

3.

4.

1

3 s + 1

s

2

1

L

(a) 3 cos(t) + sin(t) (b) e t 2 e t (c) 2 e t + e t (d) 2 e t + e t (e) None of these

=

L u ( t 3)e

(a)

e 6 e 3s

2t

=

(b) e 3s

s

+ 2

(c)

e

3s

s +

2

(d) e 6 e 3s

s + 2

(e) None of these

L

1

(a)

(b)

(c)

(d)

(e)

2s

s 2 2 s + 4

se

=

1

e t cos( 3t) + 3 e 3t sin( 3 t)

u ( t 2)e t 2 cos[ 3(t 2)] + sin[ 3(t 2)]

u ( t 2)e t 2 cos[ 3( t 2)] + 3 sin[ 3( t 2)]

1

u ( t 2)e t 2 cos[ 3( t 2)] + 3 sin[ 3( t 2)]

1

None of the above

5. Solve the initial-value problem y + y 6 y = 0 , y (0) = 1 , y Solution:

(0) = 12.

[s 2 Y ( s ) sy (0) y (0)] + [sY ( s ) y (0)] 6 Y ( s )=0

6.

s 2 + s 6 = ( s 2)(s + 3) = s 2 s + 3 by

s + 13

s + 13

3

2

(0) = 0.

( s 2 + s 6)Y ( s ) s 13 = 0 Y ( s ) =

partial fractions. Hence, y ( t)=3 e 2t 2 e 3t .

Solve the initial-value problem y + 6 y + 13 y = 0 , y (0) = 1 , y

Solution:

[s 2 Y ( s ) sy (0) y (0)] + 6[sY ( s ) y (0)] + 13 Y ( s )=0

2

( s 2 + 6 s + 13)Y ( s ) s 6=0 Y ( s ) =

s + 6

( s + 3) + 3

s 2 + 6 s + 13 = ( s + 3) 2 + 4 =

3

( s + 3) 2 + 4 + 2

s + 3

( s + 3) 2 + 4 y ( t) = e 3t cos(2 t) + 3 e 3t sin(2 t) .

2

2